Analisis implementasi akuntansi pertanggungjawaban sebagai alat penilaian kinerja pusat biaya pada Perusahaan Daerah Air Minum (PDAM) Wanua Wenang Manado - Gracia, Hana; Budiarso, Novi Swandari; Pinatik, Sherly (Manajemen Bisnis dan Keuangan Korporat, 2025)
Responsibility accounting is a system used to evaluate managerial performance in cost centers based on accountability for costs and revenues. This study analyzes the implementation of responsibility accounting in assessing cost center performance at PDAM Wanua Wenang Manado using a descriptive method, with data collected through interviews, observations, and documentation. The results show that the system has been implemented fairly well, though improvements are needed in classifying controllable and uncontrollable costs. Accountability reporting is conducted through budget-to-actual comparisons, revealing several significant budget variances.